ARF-GEF cytohesin-2/ARNO regulates R-Ras and α5-integrin recycling through an EHD1-positive compartment - Salem, Joseph C. (Mol Biol Cell, 2015)
When expressed in epithelial cells, cytohesin-2/ARNO, a guanine nucleotide exchange factor (GEF) for ARF small GTPases, causes a robust migration response. Recent evidence suggests that cytohesin-2/ARNO acts downstream of small the GTPase R-Ras to promote spreading and migration. We hypothesized that cytohesin-2/ARNO could transmit R-Ras signals by regulating the recycling of R-Ras through ARF activation. We found that Eps15-homology domain 1 (EHD1), a protein that associates with the endocytic recycling compartment (ERC), colocalizes with active R-Ras in transiently expressed HeLa cells. In addition, we show that EHD1-positive recycling endosomes are a novel compartment for cytohesin-2/ARNO. Knockdown or expression of GEF-inactive (E156K) cytohesin-2/ARNO causes R-Ras to accumulate on recycling endosomes containing EHD1 and inhibits cell spreading. E156K-ARNO also causes a reduction in focal adhesion size and number. Finally, we demonstrate that R-Ras/ARNO signaling is required for recycling of α5-integrin and R-Ras to the plasma membrane. These data establish a role for cytohesin-2/ARNO as a regulator of R-Ras and integrin recycling and suggest that ARF-regulated trafficking of R-Ras is required for R-Ras–dependent effects on spreading and adhesion formation.